2014
DOI: 10.1007/s11665-014-0965-0
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Axial Fatigue for Peripheral Nitinol Stents

Abstract: Despite their success as primary treatment for vascular diseases, Nitinol peripheral stents are still affected by complications related to fatigue failure. Hip and knee movements during daily activities produce large and cyclic deformations of the superficial femoral artery, that concomitant to the effects of pulsatile blood pressure, may cause fatigue failure in the stent. Fatigue failure typically occurs in cases of very extended lesions, which often require the use of two or more overlapping stents. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the presence of the tube plays a crucial role in affecting the initial state of the stent, albeit in a difficultly predictable way. First, it would be necessary to conduct a thorough characterization of the tube's constituent material (usually silicone or latex) for assessing its radial compliance, which is the key element in defining the equilibrium configuration at the end of the deployment [66], thus, the initial stress and strain state in the stent before cycling can be obtained [67]. Then, since remote loads are applied to the tubes, a fine calibration of the stent-tube friction properties should be addressed for a reliable description of the load quota transferred to the stent during the test.…”
Section: Fatigue Criteriamentioning
confidence: 99%
“…Indeed, the presence of the tube plays a crucial role in affecting the initial state of the stent, albeit in a difficultly predictable way. First, it would be necessary to conduct a thorough characterization of the tube's constituent material (usually silicone or latex) for assessing its radial compliance, which is the key element in defining the equilibrium configuration at the end of the deployment [66], thus, the initial stress and strain state in the stent before cycling can be obtained [67]. Then, since remote loads are applied to the tubes, a fine calibration of the stent-tube friction properties should be addressed for a reliable description of the load quota transferred to the stent during the test.…”
Section: Fatigue Criteriamentioning
confidence: 99%
“…The conclusions showed that both types of loadings play important roles in stent fatigue fracture, depending on the implantation location within the vascular tree [ 25 ]. Meoli et al analyzed the stent fatigue performance subjected to cyclic bending and compression in the fully deployed configurations [ 26 , 27 ]. Lei et al showed that the stent-to-artery oversize ratio should be considered in the fatigue analysis of a stent [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced nonlinear FE method showed its feasibility for fatigue prediction for nitinol stents in human arteries. A series of numerical studies on the risk of fatigue failure of nitinol stents were carried out by a research team at Politecnico di Milano (Italy), with a focus on the effects of failure criteria, loading conditions and plaque morphology (Petrini et al 2012(Petrini et al , 2016Meoli et al 2013Meoli et al , 2014Dordoni et al 2014;Allegretti et al 2018). Lei et al (2019) showed both atherosclerotic plaque and physiological loading conditions should be considered to accurately assess the fatigue behaviours of stents.…”
Section: Introductionmentioning
confidence: 99%